Writing Assessment Construction for Madrasah Teacher: Engaging Teacher Faith and Identity Processes - Desi Sukenti; Syahrul Ramadhan; Mukhaiyar Mukhaiyar; Syahraini Tambak (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2022)
The development of students' academic achievement in the field of Indonesian language is very urgent and for that a writing assessment is needed. The aims of this study is to analyses the involvement of faith and the identity attribution of Indonesian language teachers in developing writing assessments in madrasah. This study uses a phenomenological approach. This study are involving twenty Indonesian teachers in madrasah and conducting in-depth interviews to reveal the narrative of teachers' practices in developing writing assessments. The collected data using first experiences with informants and their reactions to those experiences, a semi-structured interview schedule was used. This study uses thematic analysis to examine the holistic meaning of phenomena through the description of subjective perceptions. The result of study shows involvement of personal morality and religiosity, attribution of identity when assessing, plays a role in the development of writing assessments in Indonesian language and literature in madrasah. The application of faith principles is the main link in the development of writing assessments, in addition to attribution of the identity of God-given personality to the assessment of writing Indonesian language and literature. The identity and writing assessment abilities of Indonesian language teachers develop with various variants, and students' skills and mastery of material also develop in improving literacy, as well as their academic achievements. In conclusion, the results of this exploratory study show that faith and personal identity attribution can develop writing assessments in the Indonesian language field.